Short Communication: Species diversity of mangrove in Kutai National Park, East Kalimantan, Indonesia - Erny Poedjirahajoe; Iin Sumbada Sulistyorini; Liris Lis Komara (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Poedjirahajoe E, Sulityorini IS, Komara LL. 2019. Short Communication: Species diversity of mangrove in Kutai National Park, East Kalimantan, Indonesia. Biodiversitas 20: 3641-3646. Kutai National Park (KNP) in East Kalimantan, Indonesia is blessed with natural mangrove forests. However, there is only very little information relating to the species composition and mangrove diversity. Therefore, this study was conducted to assess the mangrove tree species diversity and richness in Kutai National Park, East Kalimantan, Indonesia. The study results showed that the mangrove trees density was 1,214 trees/ha in the line transect vegetation survey with 1.7 ha plot. The number of mangrove species in KNP was 17 from 6 families. The dominant species with large numbers of individuals were Rhizophora mucronata, Rhizophora apiculata, and Bruguiera sexangula. The diversity index was low in mangroves in Pandan Bay Estuary, and Kaba Bay compared to that in Lombok bay’s mangroves.